Asaasa: The Cloth Metaphor for Connectedness. (15th June 2022) - Tordzro, Naa Densua
Abstract : Asaasa is not just a cloth that emerged from an old practice where remnants of fabrics or wax prints are stitched together to create a bigger piece of cloth or a piece quilt, but rather a metaphor for connectedness in life. This piece of work tells a story of migration, inequality, development, diversity, family and community through the Asaasa cloth, using it as a metaphor for connectedness as it emerges from poverty as a result of the various inequalities people face as they move from one country to the other in the Global South. Textiles are used in this article to tease out the idea of connectedness which is part of MIDEQ's aim in the context of migration in the Global South. The piece is representation of how we capture our migration experiences and communicated them through the Asaasa cloth.